Developing the COVID-19 intensive care medical equipment distribution platform: outcomes and lessons learned. Issue 2 (13th April 2021) - Akinluyi, Emmanuel Adeoluwa; Stell, David; Perera, Nayanee; Sibley-Allen, Christopher
Abstract : During the first wave of the coronavirus pandemic, the UK government took the decision to centralise the procurement, allocation and distribution of mission-critical intensive care unit (ICU) medical equipment. Establishing new supply chains in the context of global shortages presented significant challenges. This report describes the development of an innovative platform developed rapidly and voluntarily by clinical engineers, to mobilise the UK's shared medical equipment inventory, in order to match ICU capacity to dynamically evolving clinical demand. The 'Coronavirus ICU Medical Equipment Distribution' platform was developed to optimise ICU equipment allocation, distribution, collection, redeployment and traceability across the National Health Service. Although feedback on the platform has largely been very positive, the platform was built for a scenario that did not fully materialise in the UK and this affected the implementation approach. As such, it was not used to its full potential. Nonetheless, the platform and the insights derived and disseminated in its development have been extremely valuable. It provides a prototype for not only optimising system capacity in future pandemic scenarios but also a means for maximally exploiting the large amount of new equipment in the UK health system, as a result of the coronavirus pandemic. This early stage innovation has demonstrated that a system-wide pooled information resource can benefit the operations of individual organisations. It has also generated numerous lessons to be borne in mind in innovation projects.